Urinary Cotinine and Expired CO Concentrations in Women Exposed to Environmental Tobacco Smoke at Home - Herman Suryatama; Feni Fitriani; Sita Andarini; Agus Dwi Susanto; Achmad Hudoyo (Jurnal Respirologi Indonesia, 2019)
Introduction: The health effects of exposure to environmental tobacco smoke (ETS) using cotinine was a nicotine metabolite detected in urine. This should be recommended as a quantitative measurement of nicotine intake and as biomarker for ETS exposure in humans. Method: We performed a cross-sectional study to 60 ETS-exposed and 58 non ETS exposed adult women in Pasar Rebo area, Jakarta. The urinary cotinine concentrations were measured and analyzed using ELISA method, other informations were collected such as expired CO data, questionnaire regarding smoking habits of the subjects’ family members at home and respiratory health effects occured to subjects. Results: Median of urinary cotinine concentrations in ETS-exposed group were 24.65 ng/ml and 7.30 ng/ml in non-exposed group (P=0.0001). Median of expired CO in ETS-exposed group were 5.00 ppm and 3.00 ppm in non-exposed to ETS group (P=0.0001). Total amount of time (hours/day) in women exposed to ETS in their house was significantly correlated to urinary cotinine concentrations (P=0.037). The respiratory symptoms showed significant correlation with ETS exposure status (P=0.01). Time duration of last exposed to ETS had significant correlation with expired CO (P=0.004). The urinary cotinine concentrations cut-off point was 14.4 ng/ml (sensitivity=75%, specificity=74%, P=0.0001). The expired CO cut-off point was 3.5 ppm (sensitivity=75%, specificity=81%, p=0.0001). Strong and significant correlation was found between expired CO and urinary cotinine (r=0.641, P=0.0001). Conclusion: The urinary cotinine and expired CO concentration were significantly higher in women exposed to tobacco smoke at home than the non-exposed group. Urinary cotinine measurement was a sensitive, non-invasive and effective method to correlate with ETS exposure. (J Respir Indo. 2019; 39(3):140-53)